Integrated Blood Type Detector with IoT System to Improve Indonesian Red-Cross Public Health Services - Abu H. R, R. Setyo, Dennis, L (University of Respati Yogyakarta, Indonesia, 2019)
A survey held by the World Health Organization in 2008 shows that the bloodstock in Indonesia is 0.2% of the total population, which is lower than the minimum requirement for health services (2,5% of the total population). This is caused by the low quality of donor types of equipment and incompetent workers. In addition, the current regulation on blood availability monitoring seems rather complex and difficult process. The purpose of this study is to create an integrated device that is able to test the blood type and serves a database of bloodstock in several IRC to accelerate the distribution of blood between IRC and hospital. This research utilizes the Internet of Things (IoT) using a Wi-Fi module to create a device that could send data to computers using the internet. Through an experiment of 85 respondents, results showed that the accuracy of the device in detecting blood type is 96.5%. The time taken for the data to be received by the computer varies with the internet network used. The fastest data transfer was received using a 4G network, which requires only 1.9 seconds. Meanwhile, the 3G and 2G network took around 3.17 and 18.17 seconds respectively